Квантово-химические расчеты комплексов метилакрилата с тетрахлоридом титана - Бондалетова Л. И. Людмила Ивановна; Бондалетов В. Г. Владимир Григорьевич; Бондалетов О. В. Олег Владимирович; Старцева К. С. (2013, 2013)
Заглавие с экрана